Health inequalities for older people from minority ethnic groups receiving palliative care and end of life care: A scoping review protocol. - Narin Aker; Rachael Frost; Kate Walters; Emily West; Nathan Davies (PLoS ONE)
Objective The proposed scoping review aims to explore international literature on how older people from minority ethnic groups engage with and utilise palliative and end of life care, investigate the barriers and facilitators, and compare how this varies between ethnicities and health conditions. Introduction Minority ethnic groups make up substantial parts of the populations of many countries around the world. Research has found that there are disparities in access to palliative care and end of life care among minority ethnic groups. Language barriers, cultural values, and socio-demographic factors have been cited as preventing access to quality palliative and end of life care. However, it is unclear how these barriers and inequalities differ across different minority ethnic groups in different countries, and across different health conditions within these groups. Inclusion criteria The population will be older people of different minority ethnic groups who are receiving palliative or end of life care, family caregivers, and health and social care professionals. The sources of information will include quantitative, qualitative and mixed methods research, and sources that focus on minority ethnic groups' interactions with palliative and end of life care. Methods A scoping review guided by the Joanna Briggs Institute Manual for Evidence Synthesis. Searches of MEDLINE, Embase, PsycInfo, CINAHL, Scopus, Web of Science, Assia, and the Cochrane Library will be conducted. Citation tracking, reference list checking and grey literature searches will be undertaken. Data will be extracted, charted and summarised descriptively. Implications This review will highlight the health inequalities present in palliative and end of life care, the research gaps in understudied minority ethnic populations, locations where further study is required, and how barriers and facilitators differ across different ethnic groups and health conditions. The results of this review will be shared with stakeholders and will provide evidence-based recommendations for inclusive palliative and end of life care.